Prediction of Gut Microbial Community Structure and Function in Polycystic Ovary Syndrome With High Low-Density Lipoprotein Cholesterol - Zhu, Xuping; Li, Yanyu; Jiang, Yanmin; Zhang, Jisheng; Duan, Ru; Liu, Lin; Liu, Chao; Xu, Xiang; Yu, Lu; Wang, Qian; Xiong, Fan; Ni, Chengming; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Gut microbiota has been proved to be involved in the occurrence and development of many diseases, such as type 2 diabetes, obesity, coronary heart disease, etc. It provides a new idea for the pathogenesis of polycystic ovary syndrome (PCOS). Our study showed that the gut microbial community of PCOS with high low-density lipoprotein cholesterol (LDLC) has a noticeable imbalance. Gut microbiota of PCOS patients was significantly changed compared with CON, and these changes were closely related to LDLC. Gut microbiota may affect the metabolic level of PCOS patients through multiple metabolic pathways, and lipid metabolism disorder may further aggravate the imbalance of gut microbiota. Actinomycetaceae, Enterobacteriaceae and Streptococcaceae had high accuracy in the diagnosis of PCOS and the differentiation of subgroups, suggesting that they may play an important role in the diagnosis and treatment of PCOS in the future. Also, the model we built showed good specificity and sensitivity for distinguishing PCOS from CON (including L_CON and L_PCOS, H_CON and H_PCOS). In conclusion, this is the first report on the gut microbiota of PCOS with high LDLC, suggesting that in the drug development or treatment of PCOS patients, the difference of gut microbiota in PCOS patients with different LDLC levels should be fully considered.